The Correlation Between Students’ Time Management And Their English Learning Achievement At Vocational School - Roza, Mudia; Yulmiati, Yulmiati; Autila, Rani (Lembaga Penelitian dan Pendidikan Mandala, 2023)
Abstract. This study aims to see whether there is a positive correlation between students' time management and their English learning outcomes at Vocational School in Pulau Punjung or not. Thus, the researcher used correlation research in this study. The population 198 students in the X grade students of SMK N1 Pulau Punjung. However, in this research the researcher used a simple random sampling technique by randomly selecting students from each class as a trial class and as a research class. In this study, the sample 25% from the population was 50 students. The researcher used questionnaires an instrument to see students' time management and UAS scores to see students' English learning achievement. The data analysis technique was done by statistical calculation of Pearson Product Moment Correlation. The results showed that r-count = 0.439 with the interpretation of r 0.40-0.50 so that the level of relationship between the two variables is categorized as Enough Correlation. Thus it can be concluded that there is a significant correlation between students’ time management and students’ learning achievement at Vocational School in Pulau Punjung. The correlation between students time management and their English learning achievement was (0.439). Positively correlated if r-count > r-table. The value of r-table in this research is seen from the number of samples, in which the number of samples was 50 students. Based on 50 students, the value of the r-table in Product Moment with a significance level of 5% was (0.279). So the result of this research r-counted (0.439) was higher than r-table (0.279). So, Hi is accepted in this research.